Advances in Nanotheranostics I Design and Fabrication of Theranosic Nanoparticles - Dai, Zhifei; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2016)
This book highlights the recent advances in nanotheranostics from basic research to potential applications, and discusses the modular design and engineering of multiplex nanoparticles including gold nanostructures, luminescent nanoparticles, dendrimers and liposomes. Each chapter demonstrates multifunctional nanoparticles with topics covering targeting, imaging, delivery, diagnostics, and therapy as new modalities for cancer theranostics. This comprehensive book presents expert views on the latest developments in theranostic nanomedicine. It focuses on potential theranostic applications of multifunctional nanoparticles ranging from identifying noninvasively cancer cells by molecular detection, and visualizing in vivo drug delivery by means of contrast enhanced imaging, to destroying cancer cell s with minimal side effects via selective accumulation at tumor sites, and real-time monitoring therapeutic effectiveness. It also presents an interdisciplinary survey of nanotheranostics and as such is a valuable resource for researchers and students in related fields. Zhifei Dai is a Professor at the Department of Biomedical Engineering, College of Engineering, Peking University, China.
Keywords: Biomedical engineering; Biomaterials; Radiology; Medical physics; Nanotechnology; Biomedical Engineering and Bioengineering; Biomaterials; Radiology; Medical Physics; Nanotechnology